2020
DOI: 10.1128/msystems.00505-20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Rapidly Evolving SARS-CoV-2 Reveals Mosaic Pattern of Phylogeographical Distribution

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) that started in Wuhan, China, in December 2019 has spread worldwide, emerging as a global pandemic. The severe respiratory pneumonia caused by novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has so far claimed more than 0.38 million lives and has impacted human lives worldwide. However, as the novel SARS-CoV-2 virus displays high transmission rates, the underlying genomic severity is required to be fully understood. We studied the complete … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 96 publications
1
57
0
Order By: Relevance
“…Briefly, it can be concluded that the high fatality rate in Western countries as compared to India, during the lockdown, can be attributed to (1) their animal based diet which increases dysbiosis, hence increasing the pro-inflammatory cytokines resulting in cytokine storm in contrast to the Sattvic diet of the Indian culture including plant based diet and use of traditional medicine as recommended by the Ministry of AYUSH (Ayurveda, Yoga and Naturopathy, Unani, Siddha and Homeopathy), Government of India [58]; (2) the unhealthy dietary habits during lockdown, especially attributed to limited access to fresh grocery shopping, thus resulting in an increase in underlying conditions; (3) the late implementation of lockdown in contrast to the timely implementation of lockdown by the Government of India; (4) the possibility of a more virulent variant of COVID-19 strain prevalent in Western countries in comparison to that prevalent in India due to high mutation rate in the genome of SARS-CoV-2 virus [59,60] and; (5) India, being a developing country, is more exposed to infections as compared to the developed nations, thereby resulting in priming of their immune response against a wide variety of microbes leading to a better immune status than that observed in the Western population.…”
Section: Effect Of Microbiota On Covid-19 Cases During Lockdownmentioning
confidence: 99%
“…Briefly, it can be concluded that the high fatality rate in Western countries as compared to India, during the lockdown, can be attributed to (1) their animal based diet which increases dysbiosis, hence increasing the pro-inflammatory cytokines resulting in cytokine storm in contrast to the Sattvic diet of the Indian culture including plant based diet and use of traditional medicine as recommended by the Ministry of AYUSH (Ayurveda, Yoga and Naturopathy, Unani, Siddha and Homeopathy), Government of India [58]; (2) the unhealthy dietary habits during lockdown, especially attributed to limited access to fresh grocery shopping, thus resulting in an increase in underlying conditions; (3) the late implementation of lockdown in contrast to the timely implementation of lockdown by the Government of India; (4) the possibility of a more virulent variant of COVID-19 strain prevalent in Western countries in comparison to that prevalent in India due to high mutation rate in the genome of SARS-CoV-2 virus [59,60] and; (5) India, being a developing country, is more exposed to infections as compared to the developed nations, thereby resulting in priming of their immune response against a wide variety of microbes leading to a better immune status than that observed in the Western population.…”
Section: Effect Of Microbiota On Covid-19 Cases During Lockdownmentioning
confidence: 99%
“…SARS-CoV-2 isolates are distributed non-geographically with the prevalence of single nucleotide mutations as the major genomic variations. Genetic variance analyses revealed some subtypes, deleterious, and frequent mutation events in SARS-CoV-2 isolates [ [8] , [9] , [10] , [11] ]. Therefore, the emergence of new mutations in SARS-CoV-2 may force the subsequent establishment of a new escape or hijack mechanism for antivirals.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we reported a mosaic pattern of phylogenetic clustering of 95 genomes of SARS-COV-2 isolated from different geographical locations (5). Strains belonging to one country were found clustered with distant countries strains but not with the neighboring one.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the genome of SARS-CoV-2 comprises of ORF3a, ORF6, ORF7a, ORF7b, ORF8 and ORF9 genes encoding six accessory proteins, flanked by 5’ and 3’ UTRs (1). In our previous study (5), a higher mutational rate in the genomes from different geographical locations around the world by accumulation of Single Nucleotide Polymorphisms (SNPs) was reported. Even during these early stages of the global pandemic, genomic surveillance has been used to differentiate circulating strains into distinct, geographically based lineages (6).…”
Section: Introductionmentioning
confidence: 98%